Collection of cerebrospinal fluid in subdural space after aneurysmal subarachnoid hemorrhage - Mónica de la Caridad Reyes-Tápanes; Jonathan Lázaro Díaz-Ojeda; Orlando Ortega-Santiesteban (Universidad Médica Pinareña, 2020)
Introduction: subarachnoid hemorrhage, a cerebrovascular disease, is usually caused by aneurysms and is associated with significant impact on morbidity and mortality of affected patients. One of the complications derived from this disease are cerebrospinal fluid collections in the subdural space.